Restorative Justice in Criminal Law Reform in Indonesia - Vience Ratna Multi Wijaya; Ermania - Widjajanti (Faculty of Law, Universitas Pekalongan, 2021)
Restorative justice is indispensable in preventing an increase in crime. As countries in the world such as Canada, the United Kingdom and even the United Nations' 1975 Fifth Annual Session began to discuss Restorative Justice, it was expected that member states would also begin to use it in their positive laws. Restorative justice can monetize the level of capacity in the Penitentiary, reduce budget costs for the criminal justice process. Restorative justice in Indonesia began to exist in SE Kapolri, Kajari and SE MA. The main issue in this paper is